Taxes and dividend clientele: Evidence from trading and ownership structure - Lee, Yi-Tsung; Liu, Yu-Jane; Roll, Richard; Subrahmanyam, Avanidhar (Journal of Banking & Finance, 2006)
Although dividend clientele have been studied over several decades, their existence remains controversial. We study the interaction of dividends and taxes by exploiting a unique dataset from Taiwan, where the capital gains tax is zero. We find strong evidence of a clientele effect. Agents subject to high rates of taxation on dividends tend to hold stocks with lower dividends and sell (buy) stocks that raise (lower) dividends. Agents in lower tax brackets behave in the opposite manner. After legalization of repurchases in 2000, firms with higher concentrations of more heavily taxed shareholders were more apt to begin repurchase programs.